The Influence of Cultural Competence Training on Nursing Care Delivery in Diverse Populations - Faizah Hamoud Mohammed Al Shammari,; Laila Mashawi Hawas Ghazwani,; Hend Ali Alresheedi,; Hajer Ali Alresheedi,; Manal Fnaitel Alanazi,; Salwa Fnaitel Alanazi,; Hind medllah almotairi,; Alaa Eid Alonazi,; Rehab Theab Alshammari,; Badrieaha Milfy Alharbi,; Shaher Misfer Alotibi,; Saud farhan Alanazi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
In an increasingly globalized world, healthcare providers, especially nurses, are encountering culturally diverse populations at unprecedented levels. Cultural competence training has emerged as a critical strategy to enhance the ability of nurses to provide equitable, patient-centered care that respects cultural diversity. This paper explores the influence of cultural competence training on nursing care delivery, emphasizing its role in improving outcomes for diverse populations. Drawing from systematic reviews, cross-sectional studies, and qualitative research, the article highlights the importance of transcultural nursing education and the integration of cultural humility into clinical practice. Key findings underscore that cultural competence training not only improves nurses' understanding of cultural differences but also fosters communication, trust, and patient satisfaction. However, challenges such as resource limitations, the complexity of cultural dynamics, and the need for standardized training programs persist. Recommendations include embedding cultural competence in nursing curricula, leveraging virtual training platforms, and promoting continuous education for healthcare providers. Ultimately, cultural competence training is pivotal in addressing health disparities and advancing equitable healthcare delivery in multicultural societies.